Teaching of AM modulation using a state-of-the-art oscilloscope and spectrum analyzer - Ubillus Gonzales, Jorge Paul (2024)
There are some documents that deal with the use of spectral analysis of AM modulation but a joint analysis in the time and frequency domain is not found. This is why the aim of the present study was to show the benefits of using state-of-the-art oscilloscopes and spectrum analyzers for teaching carrier-present AM modulation (DSB-FC) in the time and frequency domains. For this, a spectrum analyzer, a radio frequency generator and an oscilloscope were used and we worked with different frequencies and modulation percentages. With the oscilloscope, the effective voltage (VRMS) and the peak-to-peak voltage of the pure carrier (Vcpp) and for the modulated carrier were measured, from these data the carrier power Pc and the total power PT were calculated, then the values. With the spectrum analyzer, the carrier power, total power (channel power) and the powers of the lower and upper sidebands were measured in dBm, µW and mV, and the theoretical values ​​were calculated. Finally, the corresponding percentage errors were calculated for the two types of measurements. The results showed generally very low percentage errors, with the oscilloscope the maximum error was 14.38%, while with the analyzer the maximum error was 8.99%. In conclusion, DSB-FC x-learning teaching through laboratory experiences using modern spectrum analyzers and oscilloscopes provides very good quality experiential learning.